Transesterification of Waste Cooking Oil using Calcium Loaded on Deoiled Spent Bleaching Clay as a Solid Base Catalyst - Gaanty Pragas, Maniam; Rehan, Zainol Abidin; Mohd Hasbi, Ab. Rahim (Universitas Diponegoro, 2016)
Waste cooking oil has a high potential as a raw material in biodiesel production due to its abundant availability and cheapest among other feedstock. Hence transesterification reaction is carried out using waste cooking oil in this research. The objective of this study is to synthesize and characterize the catalyst. On the other hand, deoiled spent bleaching clay impregnated with 40% CaO utilized as a catalyst. Optimization was carried out on methanol to oil molar ratio (6:1-24:1), catalyst loading (3-10 wt.%) and reaction duration (2-10 h). The catalyst of deoiled spent bleaching clay doped with 40% CaO was prepared by wet impregnation method and calcined at 500 °C for 4 hours. The catalyst shows high activity under optimum condition of 5 hours of reaction time, 12:1 of methanol to oil molar ratio with 7 wt.% of catalyst. The transesterification yields 84.7% methyl ester. Therefore, this catalyst has potential to be used in the transesterification of waste cooking oil in producing biodiesel due to its high activity.